Omega-3 fatty acid enrichment of chicken eggs: Regulation of long chain polyunsaturated fatty acid metabolism in laying hens - Neijat, Mohamed (Poultry Science, 2017)
Eggs enriched with omega-3 polyunsaturated fatty acids (PUFA), particularly the longer chain PUFA (LCPUFA, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)) can boost human consumption of these fatty acids implicated in human health. Alpha-linolenic acid (ALA) from plant seeds/oils, primarily serve as the source of omega-3 PUFA for hens, however, the scarcity of ALA-rich plants and the limited conversion of ALA to LCPUFA are challenges for egg enrichment. Two major experiments were conducted to determine potential factors regulating egg enrichment of omega-3 LCPUFA based on detailed assessment of PUFA profiles in different lipid pools of hen tissues. In experiment 1, supplementation of graded levels of hempseed products, provided ~ 0.1 to 1.3% of ALA in the diets. Experiment 2, investigated dietary supplementation of flaxseed oil (ALA-rich) and algal DHA (preformed LCPUFA), each providing similar graded levels of total omega-3 PUFA. Both ALA-containing models demonstrated a plateau in DHA enrichment of eggs at higher ALA intakes. ALA-containing diets led to high concentrations of ALA in the triacylglycerol (TAG) fraction of eggs and plasma, and the adipose tissue of flaxseed oil-fed hens. In total phospholipid (PL), particularly the phosphatidylethanolamine (PE), the levels of EPA and ALA in the yolk were linearly associated with those in the liver. In all tissues, DHA dominated the PE pool, exhibiting a plateau with a strong inverse correlation to the ratio of ALA to EPA in the liver, suggesting limited ALA availability for egg DHA enrichment. The use of algal DHA should therefore permit further accumulation of DHA in the total PL and TAG fractions of yolk. However, enrichment via preformed DHA (at 3.36% algal product) was also limited by hepatic PL resulting in more DHA and EPA being shunted to the adipose TAG, concurrent with elevated hepatic acyl-CoA synthetase (ACSL1) expression. As a function of total omega-3 PUFA intakes (regardless of source), similar levels of stearidonic acid (SDA) and particularly EPA accumulated in liver PE. Therefore, hepatic PL regulation, possibly aimed at maintaining EPA level, may potentially be limiting the amount of ALA accumulation in the same pool, hence limiting the endogenous synthesis of DHA and subsequent enrichment in eggs. === February 2017